Pelatihan Manajemen Keuangan Usaha Bagi Kelompok Mama-Mama Penjual Pinang di Expo Waena Kota Jayapura - Pascalina Van Sweet Sesa; Theo Allolayuk; Ramasoyan Arung Lamba (The Community Engagement Journal, 2023)
The Indonesian people's financial literacy level until now has not shown good condition, based on the results of a survey conducted by the Financial Services Authority (OJK) in 2019, which shows that financial management has not been implementing by the community. Mapping the level of financial literacy by employment rate, the results showed an increase in the percentage of financial literacy for all classifications of job types from 2016 to 2019, where employers were 43.60%. MSMEs are one of the sectors that have been greatly affected by the Covid-19 pandemic. The survey results showed that 77% of respondents experienced a decrease in income, 35% of whom experience a decreased in income in the range of 40%-60% (OJK, 2021). The impact of the COVID-19 pandemic, which has been confirmed from various existing surveys, confirms that financial literacy is a life skill that must be possessed by every individual today. The Business Financial Management training activity for the Betel Nut and Noken Seller Mama Group at Expo Waena aims to be able to foster scientific understanding and understanding of small business actors regarding financial literacy, especially regarding business financial management as a business actor, supporting business actors in making decisions related to business finances and their preferences and is expected to be able to manage and analyze their income and expenses so that more smart and wise in managing business finances and his personal finance. The participants in this activity were the participants who registered, namely 15 participants, and those who participated in the training activity were about 6 people from the group of betel nut and noken sellers at the waena expo in Jayapura City.Keywords: Business, Financial Management, Training